Primary source of placer gold in the Luk Ulo Metamorphic Complex, Central Java, Indonesia - Suhendra, Renaldi (Wiley-Blackwell, 2022)
The Luk Ulo Metamorphic Complex, Central Java is a product of the Cretaceous subduction and accretion, and includes diverse types of protoliths. Two-types of primary mineralization have been recognized in this area, namely, (1) seafloor basalt-hosted massive sulfide mineralization and (2) low-grade metamorphic rocks-hosted vein type mineralization. Later erosion of these types of primary mineralization formed placer gold deposits along rivers. However, the source has never been identified. Thus, this study aims at understanding the source of placer gold, the characteristics of the primary mineralization, and the tectonic evolution of the study area on the basis of mineralogy, mineral chemistry, whole-rock geochemistry, and sulfur isotope analyses. Volcanogenic massive sulfide (VMS)-type mineralization was identified in the seafloor basalt and few deep-sea sedimentary rocks, and both the ores and host rocks preserved pre-metamorphic textures and minerals. The characteristics of this VMS-type mineralization include (1) crustiform quartz veins with pyrite cutting the host rocks, (2) zonation of local silicification to interlayered chlorite/smectite-chlorite-laumontite-calcite-epidote alteration from central to outer zone, (3) pyrite-dominated ores with minor amounts of arsenian pyrite, chalcopyrite, and marcasite, (4) unmetamorphosed host rocks and ores, and (5) sulfur isotope signature with a median δ34S of +3.1‰ suggesting sulfur derived from magmatic source and/or sulfur extracted from basaltic rocks with a small contribution of biogenic sulfur. On the other hand, low-grade metamorphic rocks-hosted vein type mineralization was identified as orogenic-type gold mineralization, and the mineralized veins formed after the peak of metamorphism. It is characterized by (1) pyrite-arsenian pyrite ores with minor amounts of arsenopyrite, galena, tetrahedrite, chalcopyrite, and sphalerite, (2) quartz-illite-graphite alteration assemblage, (3) mineralized veins cross-cutting the foliation of metamorphic host rocks, (4) high antimony contents of pyrite (up to 1.7 wt) and rutile (up to 160 ppm), (5) relatively high ore-forming temperature (423 ± 9°C, calculated from arsenopyrite and graphite geothermometers), and (6) remobilized-sedimentary sulfur signature of the ores with a median δ34S of −9.8‰. Several lines of evidence suggest that placer gold was likely derived from the erosion of orogenic-type gold ores in the surrounding areas. This evidence includes the presence of gold-bearing ores hosted by low-grade metapelites and metagranitoid with characteristics of orogenic-type gold mineralization, whereas the VMS-type ores are barren in gold. The occurrence of the mid-oceanic ridge- and accretion zone-related mineralization in this area reflects the subduction and amalgamation of oceanic and continental crustal blocks during the Cretaceous period. Discovery of gold mineralization hosted in the Cretaceous basement rocks of the Sunda arc indicates the importance to broaden the gold exploration targets to include not only young volcanic rocks, but also relatively old metamorphic basement rocks. © 2022 Society of Resource Geology.